Tear Resistance, FTIR and Morphology Study of Tree Pruning Waste Papers: Effect of Soda Pulping Concentration - Lee, Zheng Xun; Low, Jiun Hor; Lim, Joon Hoong (International Journal of Integrated Engineering, 2021)
With the aim to explore the use of tree pruning waste as replacement material in papermaking, a study was conducted to investigate the effect of soda pulping concentration on the tear resistance and surface morphology of the fabricated papers. By varying the sodium hydroxide concentration from 5% to 25%, tree pruning waste papers with different tear resistance and surface morphology were fabricated. The tree pruning waste papers with the optimum tear resistance (73049.68 mN) was produced when the pulping medium was prepared at 20% sodium hydroxide concentration. As confirmed by the morphology study, the pulp fibres with improved interlocking surface morphology was produced at 20% sodium hydroxide concentration. Beyond that, fibre fibrillation had took place and exerted negative impact on the tear resistance of the papers. The present study confirms the use of tree pruning waste as an alternative in papermaking. Nonetheless, the soda pulping concentration must be properly regulated in order to maximize the performance of the fabricated paper products.